2022
DOI: 10.3389/feduc.2022.964135
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and disadvantages of distance teaching in foreign language education during COVID-19

Abstract: This article aimed to analyze the identified advantages and disadvantages of distance education in foreign language teaching in the transition to distance learning due to the COVID-19 pandemic. The data were collected through questionnaires and observations. A total of 298 university students participated in the research. The results of this research show that (1) the quality parameters of the changes and additions to the curriculum of foreign language teaching, (2) the final evaluation of the students in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Bordoloi (2018) found that open distance learning (ODL) offered the energetic grown-up population of a nation an elective path for making education accessible and for providing scope for skill-based education at minimum cost. Kruse et al. (2022) and Franklin et al.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Bordoloi (2018) found that open distance learning (ODL) offered the energetic grown-up population of a nation an elective path for making education accessible and for providing scope for skill-based education at minimum cost. Kruse et al. (2022) and Franklin et al.…”
Section: Introductionmentioning
confidence: 95%
“…Bordoloi (2018) found that open distance learning (ODL) offered the energetic grown-up population of a nation an elective path for making education accessible and for providing scope for skillbased education at minimum cost. Kruse et al (2022) and Franklin et al (1996) found that although distance learning was advantageous in a number of ways it also had a lot of limitations. For instance, students had no chance of receiving immediate feedback from their Indicators of happiness in learning of TOU enthusiasm and consequently led to higher academic achievement and desirable mental quotient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that aimed to analyze the advantages and disadvantages of distance education among undergraduate students during the pandemic, Kruse et al (2022) pointed out that the main advantage of distance learning is the formation of competencies in information technologies among teachers and students. This advantage provides excellent opportunities for access to modern electronic resources and various digital tools.…”
Section: Education and Training Practices In Rf During The Pandemic P...mentioning
confidence: 99%
“…Countries with sophisticated network infrastructure setups have switched to online teaching and have rapidly set up online learning administration systems to bring children back to the classroom. This has been an effective measure to address the shortcomings of face-to-face education during the pandemic (Kruse et al, 2022). For example, the Chinese government mandated distance learning programs for students during school closures because schools experienced huge disruptions in education in the spring of 2020.…”
Section: Introductionmentioning
confidence: 99%